Virtual reality-based cognitive–behavioural therapy for the treatment of anxiety in patients with acute myocardial infarction: a randomised clinical trial - Jiajun Weng; Junbo Ge; Jiajia Liu; Juying Qian; Xiao Huang; Yuanyuan Li; Juan Peng; Yan'e Lu; Dong Huang; Pingyuan Yang; Shikun Xu; Lihua Guan; et al. (General Psychiatry)
Background The presence of mental health conditions is pervasive in patients who experienced acute myocardial infarction (AMI), significantly disrupting their recovery. Providing timely and easily accessible psychological interventions using virtual reality-based cognitive–behavioural therapy (VR-CBT) could potentially improve both acute and long-term symptoms affecting their mental health.Aims We aim to examine the effectiveness of VR-CBT on anxiety symptoms in patients with AMI who were admitted to the intensive care unit (ICU) during the acute stage of their illness.Methods In this single-blind randomised clinical trial, participants with anxiety symptoms who were admitted to the ICU due to AMI were continuously recruited from December 2022 to February 2023. Patients who were Han Chinese aged 18–75 years were randomly assigned (1:1) via block randomisation to either the VR-CBT group to receive VR-CBT in addition to standard mental health support, or the control group to receive standard mental health support only. VR-CBT consisted of four modules and was delivered at the bedside over a 1-week period. Assessments were done at baseline, immediately after treatment and at 3-month follow-up. The intention-to-treat analysis began in June 2023. The primary outcome measure was the changes in anxiety symptoms as assessed by the Hamilton Anxiety Rating Scale (HAM-A).Results Among 148 randomised participants, 70 were assigned to the VR-CBT group and 78 to the control group. The 1-week VR-CBT intervention plus standard mental health support significantly reduced the anxiety symptoms compared with standard mental health support alone in terms of HAM-A scores at both post intervention (Cohen’s d=−1.27 (95% confidence interval (CI): −1.64 to −0.90, p<0.001) and 3-month follow-up (Cohen’s d=−0.37 (95% CI: −0.72 to −0.01, p=0.024). Of the 70 participants who received VR-CBT, 62 (88.6%) completed the entire intervention. Cybersickness was the main reported adverse event (n=5).Conclusions Our results indicate that VR-CBT can significantly reduce post-AMI anxiety at the acute stage of the illness; the improvement was maintained at the 3-month follow-up.Trial registration number The trial was registered at www.chictr.org.cn with the identifier: ChiCTR2200066435.